LAUKSAIMNIECĪBAS BIOMASAS TORIFIKĀCIJAS PROCESA IZPĒTE UN TEHNOLOĢIJAS PAMATOJUMS - Birska, Ginta (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Master's thesis is designed to demonstrate that torrefaction process involves raw agricultural biomass characteristics changes, improves its energetic parameters-calorific value, density, carbon content. Master's thesis developed an experimental facility torrefaction process research investigated biomass processing temperature on the final characteristics of the product, evaluated results of experiments with various types of biomass and mixtures thereof would result in recommendations for treatment process optimization and technological schemes offered torrefation material from biomass.